Mental Health Nursing And Shaping A Brighter Future (Journal of Namibian Studies : History Politics Culture, 2022)
This research explores the growing significance of nurse leadership in addressing mental health challenges in Canada. It highlights the concerning statistics on mental health prevalence and economic burden. The paper then discusses how nurses can make a positive impact through leadership in various areas including nursing practice, technology adoption, ensuring continuity of care, collaborating with patients to reduce stigma, and championing recovery-oriented care. The crucial role of psychiatric-mental health nursing and its evolving landscape are explored, including the importance of incorporating recovery-oriented practices, quality care standards, and minimizing seclusion and restraint. Emphasis is placed on fostering safety for both nurses and patients. The paper concludes by underlining the importance of integrating these advancements into nursing education and ongoing professional development, while advocating for the designation of Nurse Practitioner-Mental Health.